PENGEMBANGAN E-LKPD WORD SEARCH BERBASIS LIVE WORKSHEETS PADA MATA PELAJARAN BAHASA INGGRIS UNIT 11 KELAS IV DI SEKOLAH DASAR - Jannah, Allyah Miftahull; Lubis, Wildansyah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
This research aims to develop an E-LKPD Word Search Based on Live Worksheets for the English Subject Unit 11 Class IV Elementary School which is declared suitable for use based on validity, practicality and effectiveness tests. This research is a type of Research and Development (R&D) research with the ADDIE model which consists of 5 stages. The validity of E-LKPD is known from the results of the E-LKPD material validator with a gain of 96% and the E-LKPD media validator 91%. Practicality is known from the results of educational practitioner questionnaires of 94% and student responses of 94% after product trials were carried out. The effectiveness of E-LKPD is known from the percentage of student learning completion of 82% with an N-Gain of 0.65. So E-LKPD Word Search Based on Live Worksheets in English Subjects is suitable for use.